E-Payment in The Eyes of Students: Analyzing the Impact of Trust, Risk, Benefits and Income - Akbar, Hardhan Syaifullah; Ikhlash, Muhammad; Halim, Muhammad Irsyad; Esmeralda, Angel II P. (Social Sciences Insights Journal, 2023)
This research aims to determine the influence of a person's beliefs, risks, benefits, and income on interest in using e-payment, especially for Politeknik Negeri Batam students. This is quantitative research that uses non-probability sampling and collects respondent data using a Google Drive form, which will then be processed using IBM SPSS Statistics 23. The population of this research is active Politeknik Negeri Batam students who have used online payment methods or e-payments, with a total of 97 samples. The results of the tests carried out in this research show that trust has a negative effect and does not have a significant effect on a person's interest in using e-payment. Risk has a positive and significant effect on a person's interest in using e-payments. Benefits have a positive and significant influence on a person's interest in using e-payment. Income has a positive and significant effect on a person's interest in using e-payments.